Association Between Anesthesia Exposure and Neurocognitive and Neuroimaging Outcomes in Long-term Survivors of Childhood Acute Lymphoblastic Leukemia - Banerjee, Pia (JAMA Oncol, 2019)
IMPORTANCE: Limited studies have reported associations between anesthesia and neurocognitive and neuroimaging outcomes, particularly in pediatric patients who undergo multiple exposures to anesthesia as part of chronic disease management. OBJECTIVE: To investigate whether general anesthesia is associated with neurocognitive impairment and neuroimaging abnormalities in long-term survivors of childhood acute lymphoblastic leukemia. DESIGN, SETTING, AND PARTICIPANTS: A cohort study of 212 survivors of childhood acute lymphoblastic leukemia who received treatment between July 7, 2000, and November 3, 2010, and follow-up at a mean (SD) of 7.7 (1.7) years post diagnosis, was conducted at an academic medical center. Of 301 survivors who were alive and eligible for participation, 217 individuals (72.1%) agreed to participate in long-term follow-up. Data analysis was performed from August 23, 2017, to May 3, 2018. EXPOSURES: For 5699 anesthesia procedures, data on duration and cumulative doses of all anesthetics, sedatives, analgesics, anxiolytics, and neuromuscular blockers were abstracted, along with cumulative doses of high-dose intravenous methotrexate and number of triple intrathecal chemotherapy treatments. MAIN OUTCOMES AND MEASURES: Neurocognitive measures of attention, processing speed, executive function, and intelligence were examined. Brain volumes, cortical thickness, and diffusion tensor imaging of the whole brain, corpus callosum, frontal lobes, and parietal lobes were evaluated. RESULTS: Of the 217 study participants, 212 were included in both neurocognitive and brain imaging analysis. Of these, 105 were female (49.5%); mean (SD) age at diagnosis was 14.36 (4.79) years; time since diagnosis was 7.7 (1.7) years. Adjusting for chemotherapy doses and age at diagnosis, neurocognitive impairment was associated with higher propofol cumulative dose (relative risk [RR], 1.40 per 100 mg/kg; 95% CI, 1.11-1.75), flurane exposure (RR, 1.10 per exposure; 95% CI, 1.01-1.21), and longer anesthesia duration (RR, 1.03 per cumulative hour; 95% CI, 1.00-1.06). Slower processing speed was associated with higher propofol dose (estimate [est], −0.30; P = .04), greater number of exposures to fluranes (est, −0.14; P = .01), and longer anesthesia duration (est, −0.04; P = .003). Higher corpus callosum white matter diffusivity was associated with dose of propofol (est, 2.55; P = .01) and duration of anesthesia (est, 2.40; P = .02). Processing speed was significantly correlated with corpus callosum diffusivity (r = −0.26, P < .001). CONCLUSIONS AND RELEVANCE: Higher cumulative anesthesia exposure and duration may be associated with neurocognitive impairment and neuroimaging abnormalities in long-term survivors of childhood acute lymphoblastic leukemia, beyond the known outcomes associated with neurotoxic chemotherapies. Anesthesia exposures should be limited in pediatric populations with chronic health conditions who undergo multiple medical procedures.